2023
DOI: 10.1108/agjsr-12-2022-0281
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Covid-19 on consumer behaviour: a bibliometric review analysis and text mining

Abstract: PurposeThis paper is a bibliometric analysis of articles published on the influence of Covid-19 on consumer behaviour.Design/methodology/approachBiblioshiny and VOSviewer applications are employed for the bibliometric analysis and visualisation, respectively.FindingsThe most influential documents, authors, affiliations, countries and journals are presented. Citation, Co-citation and keyword co-occurrence analysis is conducted and presented in the form of a clustered network diagram.Practical implicationsThis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
4
0
1
Order By: Relevance
“…The positive impact of product consumption satisfaction on product continuance of consumption has been confirmed by Kaewkitipong et al (2016), andHsu et al (2016) have shown that it is a catalyst that motivates consumers to continue with consumption. Literature also shows that product consumption satisfaction plays a vital role in inciting consumers to continue consuming the product (Yassierli et al, 2019;Bashar et al, 2023). Based on the literature and empirical evidence, it is hypothesized that:…”
Section: Product Consumption Satisfaction and Continuance Of Cereal C...mentioning
confidence: 99%
“…The positive impact of product consumption satisfaction on product continuance of consumption has been confirmed by Kaewkitipong et al (2016), andHsu et al (2016) have shown that it is a catalyst that motivates consumers to continue with consumption. Literature also shows that product consumption satisfaction plays a vital role in inciting consumers to continue consuming the product (Yassierli et al, 2019;Bashar et al, 2023). Based on the literature and empirical evidence, it is hypothesized that:…”
Section: Product Consumption Satisfaction and Continuance Of Cereal C...mentioning
confidence: 99%
“…The COVID-19 coronavirus has wreaked havoc on the global economy before the eyes of the entire world. The virus not only impacted business operations but also compelled the closure of numerous establishments due to social distancing and lockdown measures [ 64 , 65 , 66 , 67 ]. Concerning employees, this led to psychological challenges stemming from job loss, reduced income, and uncertainty about the future [ 67 ].…”
Section: Changes In Consumer Buying Behavior In the Face Of The Covid...mentioning
confidence: 99%
“…The virus not only impacted business operations but also compelled the closure of numerous establishments due to social distancing and lockdown measures [ 64 , 65 , 66 , 67 ]. Concerning employees, this led to psychological challenges stemming from job loss, reduced income, and uncertainty about the future [ 67 ]. The rise in food prices during a period of declining incomes poses a significant problem for consumers [ 68 ].…”
Section: Changes In Consumer Buying Behavior In the Face Of The Covid...mentioning
confidence: 99%
“…Many consumers have turned to more sensible shopping and have oriented themselves towards sustainable products that contribute more to environmental protection [149]. In addition to purchasing sustainable products, consumers have followed a sustainable concept of food consumption, where less household waste has been generated [150] Consumers are buying sustainable products more frequently and are more willing to pay a premium for them. They are also becoming increasingly attentive to environmental issues and are exhibiting more sustainable behaviors [151].…”
Section: Peer Review 16 Of 30mentioning
confidence: 99%